PENGALAMAN PERSIAPAN KEHAMILAN IBU PRIMIGRAVIDA DI KABUPATEN SIDENRENG RAPPANG: PREGNANCY EXPERIENCE OF PRIMIGRAVIDA MOTHERS IN SIDENRENG RAPPANG REGENCY - Hamsir, Andi Basmalah; Asfarada, Muhammad Rizky; Zakiyah, Alifah Ummu (Ikatan Lembaga Mahasiswa Ilmu Keperawatan Indonesia, 2023)
Introduction: Treatment in preparation for pregnancy usually includes a physical examination, supporting examinations, immunization, nutritional supplementation, and health consultation. One of the puskesmas that implements care in preparation for pregnancy is the Manisa Health Center in Sidenreng Rappang Regency. However, these services are still classified as limited because they are not by the program issued by the Ministry of Health.Methods: This research uses a qualitative study with a phenomenological approach through in-depth interviewtechniques. Participants in this study amounted to 13 people who were selected by purposive sampling.Result: The results of the theme analysis are (1) independent efforts to prepare for pregnancy, (2) limitedhealth services in preparation for pregnancy, (3) traditional medicine in preparation for pregnancy.Conclusion: The independent efforts of primigravida mothers are supported by their families and thepeople around them. Participants visited the health service for a tetanus toxoid injection. In addition, someparticipants visited several areas to perform traditional medicine.